Student Learning Independence in Online Learning of Economic and Business English Course using Moodle - Regi Esa Sura Pratama (Buana Pendidikan, 2023)
This study aims to describe student independence in online learning of English subjects. The research approach used is descriptive qualitative research. The subject and object of research focusing on 2nd-semester students of the Accounting Department and 3rd-semester students of the Management Department at STIE Kesumanegara Blitar. Data collection in this study was carried out through interviews, online questionnaires, and a literature study. The study results show that: (1) 50 out of 67 respondents often or sometimes ask for help from others when online learning; (2) According to their initiative shows results that are classified as low student awareness; (3) 47 students asking for help from lecturers and friends when they have difficulty learning; and (4) the level of student discipline in online learning is classified as good. It can be concluded that the student independence level in online English learning is still low and is included in the dependent category.